Development and Reliability of the Prospective Memory Assessment for Children & Youth (PROMACY): A Preliminary Study in a Non-Clinical Sample - Garvie, Patricia A. (Appl Neuropsychol Child, 2018)
Prospective memory (PM), “remembering to remember,” has been linked to important functional outcomes in adults. Studies of PM in children and adolescents would benefit from the development and validation of developmentally appropriate clinical measures with known psychometric properties. The Prospective Memory Assessment for Children & Youth (PROMACY), a performance-based measure of PM, was developed for the Pediatric HIV/AIDS Cohort Study Adolescent Master Protocol, Memory and Executive Functioning Substudy, and includes Summary, Time-, and Event-based scores derived from eight trials with an ongoing word search task. Fifty-four healthy perinatally HIV-exposed, uninfected children and youth, mean age 13 years, 54% female, 76% Black/non-Hispanic, and 61% impoverished were included in this psychometric analysis. PROMACY Summary Scores demonstrated low, but broadly acceptable internal consistency as measured by Cronbach’s alpha and Spearman-Brown. Better PROMACY performance was associated with older age, but no other demographic factors. Generally medium-sized correlations were observed between the PROMACY Summary Score and standard clinical measures of retrospective memory, working memory, executive functions, and IQ. Findings from this preliminary psychometric study of non-clinical children and youth provide cautious support for the internal consistency and construct validity of PROMACY’s Summary Score that awaits replication and extension in larger samples of healthy children, youth and clinical populations.